Analysis of Vertical Load Transfer Mechanism of Assembled Lattice Diaphragm Wall in Collapsible Loess Area. (8th July 2021) - Xia, Mingtan; Zhang, Xudong; Yang, Gengshe; Hui, Liu; Ye, Wanjun
Abstract : Based on analysis of the formation mechanism and characteristics of the negative friction in collapsible loess areas, this study investigates the load transfer law of a wall-soil system under a vertical load, establishes the vertical bearing model of a lattice diaphragm wall, and analyzes the vertical bearing capacity of an assembled latticed diaphragm wall (ALDW) in a loess area. The factors influencing the vertical bearing characteristics of the ALDW in a loess area are analyzed. The vertical bearing mechanism of the lattice diaphragm wall in the loess area is investigated. The failure modes of the ALDW in the loess area are mainly shear failure of the soil around the wall and failure of the wall-soil interface. In the generation and development of negative friction, there is always a point where the relative displacement of the wall-soil interface is zero at a certain depth below the ground; at this point, the wall and soil are relative to each other. The collapsibility of loess, settlement of the wall and surrounding soil, and rate and method of immersion are the factors affecting the lattice diaphragm wall. The conclusions of this study provide a reference for the design and construction of ALDWs in loess areas.